2011
DOI: 10.1063/1.3604017
|View full text |Cite
|
Sign up to set email alerts
|

Observation of coherently enhanced tunable narrow-band terahertz transition radiation from a relativistic sub-picosecond electron bunch train

Abstract: We experimentally demonstrate the production of narrow-band (df =f % 20% at f % 0:5 THz) transition radiation with tunable frequency over [0.37, 0.86] THz. The radiation is produced as a train of sub-picosecond relativistic electron bunches transits at the vacuum-aluminum interface of an aluminum converter screen. The bunch train is generated via a transverse-to-longitudinal phase space exchange technique. We also show a possible application of modulated beams to extend the dynamical range of a popular bunch l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…Recently, it has been demonstrated that it is possible to generate tunable, narrowband, few-cycle, and multicycle coherent THz radiation by properly shaping the longitudinal charge distribution of the electron beam. Different approaches are currently used: a temporally shaped photocathode drive laser pulse, 16, 17 a mask in a high dispersion, low beta function region of a beamline dogleg in order to produce a temporal bunch train out of a long bunch with a correlated energy spread, 18 a transversely segmented beam (with a multislit mask) manipulated via a transverse-to-longitudinal phase space exchange technique, 19 and an ultra-short relativistic electron bunch passing through a magnetic undulator. 20 For instance, molecular spectroscopy and imaging can benefit from a high peak power, tunable THz radiation with narrow spectral bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that it is possible to generate tunable, narrowband, few-cycle, and multicycle coherent THz radiation by properly shaping the longitudinal charge distribution of the electron beam. Different approaches are currently used: a temporally shaped photocathode drive laser pulse, 16, 17 a mask in a high dispersion, low beta function region of a beamline dogleg in order to produce a temporal bunch train out of a long bunch with a correlated energy spread, 18 a transversely segmented beam (with a multislit mask) manipulated via a transverse-to-longitudinal phase space exchange technique, 19 and an ultra-short relativistic electron bunch passing through a magnetic undulator. 20 For instance, molecular spectroscopy and imaging can benefit from a high peak power, tunable THz radiation with narrow spectral bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to enable the THz radiation source tunability and its stable operation, 1-5 the accurate knowledge of the distance between bunches is also required, as the spacing between micro-bunches defines the spectrum of the radiation. [18][19][20][21][22][23][24] In both examples and in other applications driven by such beams, the development of a non-invasive, a single-shot system capable of monitoring the distance between micro-bunches is important, and in many cases, non-destructive, single-shot evaluation of the bunch-to-bunch distance is still an unresolved challenge. At present, the most popular techniques used to study micro-bunch separations are via measurements of autocorrelation functions 2,18,19 and use of a transverse deflection cavity.…”
mentioning
confidence: 99%
“…At present, the micro-bunched beam can be generated by a beam in the following techniques: modulation in a plasma channel, 6-8,10-12 "slicing," 2,3,18 seeded instability, 4,13,14 and directly from a photocathode. 5,19,25,26 In all of these techniques, the final spacing between micro-bunches can vary from shot to shot. Here (for reasons of clarity only), we will focus on the generation of the micro-bunches directly from a photocathode.…”
mentioning
confidence: 99%
“…Possible methods include the use of a shaped mask in a dispervise section [15,16], the mapping of a transversely-shaped beam into the temporal axis using a transverse-to-longitudinal phase-space exchanger [17] or the use of nonlinear longitudinal manipulation [18,19]. Here we point out that the passive technique described in the this paper can be used to form beams with tailored current profiles.…”
Section: Bunch-current Shapingmentioning
confidence: 94%